1950-talets ting och minnen - Gunnemark, Kerstin (Tidsskrift for kulturforskning, 2009)
The purpose of this article is to describe the strategies of a small museum which has a focus on narratives and dialogues. Kortedala Museum in Gothenburg was the first museum in Sweden to represent an ordinary home in a modern suburb in the period 1955-1965. Thus, it is not a museum which gives attention to famous neighbours or local historical events. The main purpose is to illustrate the materialisation of the concept of the People's Home, (folkhemmet in Swedish), and its realisation in a new built area in the middle of the 20th century. In this respect this small museum emphasizes a national policy which gave many Swedish households the opportunity to live in apartments with modern equipment for the first time in their lives.